The negative effect of flaxseed oil on reproduction through its effect on spermatogenesis and ovulation in mice - Ahmed Badr Abdulwahid Alfadhli; Assad Hassan Eissa Aledany; Nehaya Mnahi Tari Al-Aubody; Hadeel Salman Hussein Al Ali (International Journal of Medical Toxicology and Legal Medicine, 2025)
Objectives: Infertility is defined as failure to achieve pregnancy after 12 months of sexual intercourse without any contraceptive measures. Flaxseed oil has broad spectrum uses in health aspects. It has been getting a special attention in treatment of infertility. The aim of our study is to evaluate the effect of flaxseed oil on fertility in mice Methods: The study included seventy-five mice (Bulbe C). Each gender of mice was randomly divided into three groups, one group serves as control group while the other two groups were treated with flaxseed oil extract with either a dose of 60 mg /Kg BW/ day or a dose of 120 mg /Kg BW/ day for 2 weeks. At the end of treatment period the animals were redistributed in a way that each female group was subjected to mate with male mice from the three male groups to study the reproductive efficiency alteration by flaxseed oil extract. Results: There was no pregnancy in all groups treated with flaxseed oil and azoospermia in all treated male groups with serious histological changes in testes and epididymis. Conclusion: There was obvious negative effect for flaxseed oil on the reproduction in male and female mice regarding pregnancy percentage, sperm count and histological changes of testis and epididymis.